1990
DOI: 10.1007/bf01304705
|View full text |Cite
|
Sign up to set email alerts
|

Effective boson number calculations in Mo and Cd isotopes

Abstract: The effects of the neutron-proton interaction on the low-lying levels of Mo and Cd isotopes have been considered in the frame of the IBA-1 model by taking into account an effective boson number (Neff). Both an empirical procedure based on previous IBA-2 mixing calculations and the Np AT, scheme provide comparable Neff values. Level spectra and electromagnetic transitions are investigated. The results support the idea that IBA-1 calculations with a suitable Neff can largely simulate IBA-2 mixing calculations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The shape transition in the Ru isotopes is from a vibrational [U (5)] limit in the lighter isotopes to a y-unstable [O (6)] limit in the heavier isotopes [3]. But, the shape transition in the Mo isotopes is known [4] to be from a vibrational limit in Mo to a rotational limit in ' ' Mo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape transition in the Ru isotopes is from a vibrational [U (5)] limit in the lighter isotopes to a y-unstable [O (6)] limit in the heavier isotopes [3]. But, the shape transition in the Mo isotopes is known [4] to be from a vibrational limit in Mo to a rotational limit in ' ' Mo.…”
Section: Introductionmentioning
confidence: 99%
“…But, the shape transition in the Mo isotopes is known [4] to be from a vibrational limit in Mo to a rotational limit in ' ' Mo. The Mo isotopes have been investigated in the framework of IBM-1 assuming an effective boson number derived from either configuration mixing or an N"Ns cheme [5]. The parameter y, which is related to quadrupole strength, has a large negative value, g= - 1.…”
Section: Introductionmentioning
confidence: 99%
“…We set the boson number N B = 10, but otherwise followed Refs. [21,22], where we took the mixing compositions from. Fig.…”
mentioning
confidence: 99%
“…Their results were in good agreement with the known properties of these nuclei. As an alternative to configuration-mixing calculations within the IBM-2, Cata et al [20] studied the effects of proton-neutron interactions on the even-even Mo isotopes using the IBM-1 framework assuming an effective boson number N eff derived either from the IBM-2 parametrization of [19] or from the N ν N π systematics by Casten [21]. They concluded that IBM-1 calculations with a suitable N eff can largely simulate the IBM-2 mixing calculations, yet keeping the advantage of simplicity and less parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present the results of the application of the MAVA to even-even 94-100 Mo isotopes. A comparison of the calculated level energies and electric decay properties with the IBA results is done in detail for 94,100 Mo [20,25]. In Section 2 we outline briefly theoretical aspects and the numerical application to Mo isotopes.…”
Section: Introductionmentioning
confidence: 99%